Influence of simultaneous addition of MnO2 and CoO on properties of SnO2-based ceramics - Dibb, A.; Tebcherani, S. M.; Lacerda, W.; Santos, MRC; Cilense, M.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2000)
This paper reports on a study of the: effect of replacing CoO by MnO2 on the sintering and electrical propel-ties of the 98.95% SnO2 + (1 - x)% CoO + x% MnO2 + 0.05% Ta2O5 system. All the samples were compacted into pellets and sintered at 1300 degrees C for 1 h, when they reached densities of about 98% of the theoretical density. An X-ray diffraction (XRD) analysis showed no other detectable phases other than SnO2. Current-voltage characterization indicated varistor behavior in the systems. The non-linear coefficient (alpha) and breakdown electric field (Eb) increased as the amount of MnO2 was increased. The results are explained in terms of an electric barrier modification, due to the presence of adsorbed negative oxygen species at the grain boundary inter face. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: tin dioxide; varistors; dense ceramics; breakdown electric fields